A complex biogeographic history of diversification in Neotropical lancehead pitvipers (Serpentes, Viperidae). (12th December 2019) - Hamdan, Breno; Guedes, Thaís B.; Carrasco, Paola A.; Melville, Jane
Abstract: Based on the literature, we had predicted that the diversification within the Neotropical snake genus Bothrops occurred along a latitudinal gradient from north to south, with diversification into unoccupied niches through ecological opportunity, not correlated with geoclimatic events. Using a dated phylogeny and estimating likelihoods of ancestral states at cladogenesis events, we reconstructed ancestral areas and assessed major events of the diversification of Bothrops clades, and we also discuss systematic implications for this group. Based on the phylogeny we produced, B. lojanus was not considered as part of the genus Bothrops since the results recovered this species nested within the Bothrocophias clade. We infer that the diversification of the Miocene Bothrops pictus and Bothrops alternatus clades may be related to the uplift of the western slopes of the Andes and the Argentinian Patagonian Andes, respectively. The Pliocene Bothrops taeniatus and Bothrops osbornei clades may be related to the uplift of the eastern and northern Andes, respectively. The Plio‐Pleistocene Bothrops neuwiedi clade may be related to the habitat transitions from a warmer and forested environment to a cooler and open landscape; the Bothrops jararaca (i.e. island endemic species) and Bothrops lanceolatus clades to over‐water dispersal with island speciation; and Bothrops atrox clade to the appearance of the Panamanian land bridge. We found that a multitemporal and multidirectional history of diversification may be correlated with geoclimatic and dispersalist events. We argue that the vacant niche hypothesis by itself does not explain Bothrops diversification.